Photocontrolled On‐Surface Pseudorotaxane Formation with Well‐Ordered Macrocycle Multilayers. Issue 40 (19th August 2016) - Schwarz, Felix B.; Heinrich, Thomas; Kaufmann, J. Ole; Lippitz, Andreas; Puttreddy, Rakesh; Rissanen, Kari; Unger, Wolfgang E. S.; Schalley, Christoph A.
Abstract: The photoinduced pseudorotaxane formation between a photoresponsive axle and a tetralactam macrocycle was investigated in solution and on glass surfaces with immobilized multilayers of macrocycles. In the course of this reaction, a novel photoswitchable binding station with azobenzene as the photoswitchable unit and diketopiperazine as the binding station was synthesized and studied by NMR and UV/Vis spectroscopy. Glass surfaces have been functionalized with pyridine‐terminated SAMs and subsequently with multilayers of macrocycles through layer‐by‐layer self assembly. A preferred orientation of the macrocycles could be confirmed by NEXAFS spectroscopy. The photocontrolled deposition of the axle into the surface‐bound macrocycle‐multilayers was monitored by UV/Vis spectroscopy and led to an increase of the molecular order, as indicated by more substantial linear dichroism effects in angle‐resolved NEXAFS spectra. Abstract : Solution versus surface : A photocontrolled pseudorotaxane formation was carried out in solution and on glass surfaces with the macrocycles being immobilized in ordered, metal‐coordinated, multilayers (see scheme). Angle‐resolved NEXAFS spectra reveal these surfaces to exhibit a preferential orientation of the macrocycles, with more pronounced linear dichroism effects upon photoinduced binding of the axle.